Factors Influencing Interpersonal Interactions among Students from Different Nationalities Using English Language as the Primary Means of Their Daily Communication - Sarwari, Abdul Qahar; Muhammad Nubli, Abdul Wahab; Mohamad Hilmi, Mat Said (AWEJ.org, 2023)
This study evaluated factors influencing interpersonal communication among local and international students of a Malaysian public university. The embedded design of mixed methods was applied to conduct this study. This study had 220 participants from both local and international students of the mentioned university. Based on their agreements, 12 participants were interviewed to strengthen the survey data. Based on the results, the participants were using the English langue as the primary means of their daily interactions with their peers from different nationalities, and the levels of their English language proficiency and their daily interpersonal communication had mutual effects on each other. According to the results, around 80% of the participants had experienced some interactions with students from other nationalities at the university campus. Based on the results, their daily interactions helped the participants to improve their English language proficiency and to gain some new social and cultural information about different people.